2D and 3D in vitro photodynamic activities of tetra-substituted symmetric water-soluble cationic zinc(II) phthalocyanines on cancer - Isik, Seyma; Ozcesmeci, Mukaddes; Burat, Ayfer Kalkan; Hamuryudan, Esin; Erdogmus, Ali; Can, Ozge; Serhatli, Muge (NATURE PORTFOLIO, 2025)
In this study, the PDT activities of 2,9(10),16(17),23(24)-tetrakis(2-dimethylammoniumethoxy) phthalocyaninatozinc(II) tetraiodide (ZnPc1) and 1,8(11),15(18),22(25)-tetrakis(2-trimethylaminoethoxy)phthalocyaninatozinc(II)tetraiodide (ZnPc2) compounds were investigated in 2D monolayer cultures and 3D spheroids of three human cancer cell lines: human submaxillary salivary gland epidermoid carcinoma (A253), human colon colorectal adenocarcinoma (HT29), and human pharynx squamous carcinoma (FaDu) cells. The results indicate that both molecules are non-toxic in the absence of light, which is a crucial feature of an effective photosensitizer. Upon exposure to light, ZnPc1 exhibited significant cytotoxicity in all three cell lines, particularly in FaDu cells, in both 2D monolayer cultures and 3D spheroids, whereas ZnPc2 showed moderate efficacy compared to ZnPc1. PDT using both phthalocyanine (Pc) molecules resulted in substantial reactive oxygen species (ROS) production. Delayed ROS production is higher than that of immediate ROS, indicating their ability to stimulate ROS production over an extended period and retain an oxidative stress response in the cells rather than immediately after PDT. Among these molecules, ZnPc1 induced both immediate and delayed ROS production more efficiently than ZnPc2. Furthermore, singlet oxygen yields of ZnPc1 were higher than ZnPc2, which is consistent with the cytotoxicity results. These findings confirmed that PDT induces an ROS-mediated cytotoxic response. The mechanisms of cellular death triggered by PDT were evaluated, and the results revealed that apoptosis was the predominant process. These findings underscore the potential of ZnPc1 as a potent photosensitizer in PDT while also highlighting the differences between 2D and 3D culture models in evaluating PDT efficacy. While the 2D system enables simplified cytotoxicity evaluation, the 3D spheroid model better replicates physiologically relevant environment and treatment resistance. This comparison underscores necessity of integrating 3D models in PDT studies for more predictive in vivo insights.
Keywords: Cancer; Photodynamic therapy; Phthalocyanine; Reactive oxygen species; Singlet oxygen; DNA-BINDING; THERAPY; PATHWAYS; CELLS; PHOTOSENSITIZERS; DERIVATIVES; APOPTOSIS; FUTURE; Science & Technology - Other Topics